Determination of the vertical profile of aerosol chemical species in the microscale urban environment. (December 2018) - Chen, Yu-Chieh; Chang, Chih-Chung; Chen, Wei-Nai; Tsai, Yu-Jen; Chang, Shih-Yu
Abstract: This study developed a lightweight air composition measuring equipment (ACME) mounted in unmanned aerial vehicles (UAVs) to measure the vertical distribution characteristics of PM2.5 chemical species in the micro-scale urban environment for the first time. 212 samples collected from 0 to 350 m above ground level were analyzed for water-soluble ions. The concentrations of most ions on the above ground level were higher than that on the ground surface during the sampling period. The measurements of the total ion concentrations were approximately 54 to 26% of the PM2.5 mass concentrations on the ground surface. The concentrations of NH4 + and NO3 − decreased with increases in the height from the ground, which may be related to the influence of the vehicle emissions and human activities. NO2 − and SO4 2− both had a peak concentration on the higher vertical altitude at night in the sea-land wind system. In the southern wind system, the emissions of sea salts, dust, and stationary pollution, might be transported by the regional prevailing airflow from the southern coastal area, were the major pollutant sources above the boundary layer. The vertical distribution of ionic concentrations and wind field provided information concerning changes in pollutant transport and source regions that affect the local air quality. The ACME mounted in UAVs is the feasible and convenient method to fast understand the vertical distributions of aerosol chemical species. It provides important information about the accumulation and diffusion effects by the boundary layer variation to aerosol characteristics, which is difficulty observed from the conventional ground-based measurements. In future, this technology is the useful application for investigating the pollutant species emitted from the smokestack and the sudden pollution accident. Graphical abstract: Image 1 Highlights: A novel technology was used to measure the vertical profile of ion concentrations. The concentrations of NH4 + and NO3 − decreased with increases in the height. NO2 − and SO4 2− had peak concentrations on the higher vertical altitude at night. Sea salt, dust and stationary pollution were the major sources above the boundary. Boundary effect on aerosol profile was difficulty observed by ground measurement. Abstract : This study successfully developed a light-weight aerosol sampler to measure the vertical distribution characteristics of chemical species in PM2.5 .